Democracy and Stiffened Media Freedom in Nigeria - Dinebari David Vareba; Fashion Zabbey (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
The world over, media freedom is an essential pillar of democracy. A sacred institution that is responsible for informing the citizens of the successes and failures of government, the articulator of the people’s needs and desires to the government, and the provider of a platform for the open exchange of information and ideas. The media promotes change, informs and educates the public, and also persuades and entertains the masses on a variety of issues. The media is essential in promoting good governance, especially in a democratic setting. The media can contribute a lot to improving the government’s accountability, transparency, rule of law, more efficient markets, and a more informed society. However, reality has revealed a huge gap between the theory of ideal democratic principles that recognise media freedom and the praxis of non-interference in the delivery of the mandate of the media profession in Nigeria. Every passing day, the stiffening of the freedom of the media is felt by the citizens in different forms, including but not limited to: restriction of access to platforms to disseminate and receive information; unwarranted media regulations; harassment and intimidation of journalists, among others. This paper, therefore, sets out to examine and critically analyse the role of the mass media in promoting good governance in Nigeria. The paper determines the extent to which the media, whether print, electronic, or the new media, can be used to promote good governance in Nigeria in this present political dispensation and also provides some recommendations on how best to use the media to make the government accountable to the citizens. The paper therefore recommends that the Nigerian government should allow the media to operate without any form of unjust restraint, as they are the watchdogs of every society. They constantly monitor political, socio-cultural, and economic trends and report back to society.